Quartz fiber toughened alumina-carbon refractory material and preparation method thereof
By introducing quartz fibers into aluminum-carbon refractory materials and forming mullite layers, the problem of easy damage to the material in extreme environments is solved, the mechanical strength and high temperature stability of the material are improved, and high strength, good toughness and long life are achieved. effect.
Patent Information
- Application Number
- CN202411540490.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
Existing aluminum-carbon refractory materials are prone to microcracks and corrosion in extreme use environments, resulting in material failure, and the fibers do not bind closely to the interface between the aggregate and the matrix, which affects the mechanical properties and service life.
The mixing process of quartz fiber and sintered corundum, carbon black, boron carbide and silicon powder is adopted. The quartz fiber is evenly distributed through the closed-type strong high-thermal mixing process, and forms a mullite layer with the matrix to enhance the interface and improve the Mechanical strength and high temperature stability of the material.
The high strength, toughness, excellent thermal shock resistance and long service life of aluminum-carbon refractory materials are achieved, avoiding the problems of easy oxidation at high temperatures and intimate interface bonding in traditional fiber reinforced materials.
Smart Images

Figure CN119263787A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum-carbon refractory materials, and specifically relates to an aluminum-carbon refractory material toughened by quartz fiber and a preparation method thereof. Background Art
[0002] In the actual steelmaking process, aluminum-carbon refractory materials, as important molten steel flow control components, will be exposed to more extreme use environments, such as slag erosion, mechanical erosion of molten steel, and thermal shock. These harsh environments will lead to the generation of microcracks and critical corrosion behavior, and even worse, in extreme cases, will lead to sudden failure of aluminum-carbon refractory components. Therefore, it is of great significance to further improve the performance of aluminum-carbon refractory materials and extend their service life.
[0003] For example, the patented technology of "A multi-fiber reinforced magnesium aluminum carbon refractory material and its preparation process" (CN201710737652.7) uses dead-burned magnesia fine powder, binder, metal aluminum powder and nano iron powder as raw materials, and obtains green bodies through mixing, stirring, cold isostatic pressing, and then obtains multi-fiber reinforced magnesium aluminum carbon refractory materials through high-temperature sintering. Although this technology strengthens the mechanical properties of the material, the MgAl2O4 fibers and carbon nanotube fibers generated by it are unevenly distributed, and the diameter of the fibers is at the nanometer level, which makes it difficult to produce a good interface bonding between the aggregate and the matrix in the refractory material. When encountering stress concentration, it cannot disperse the stress well, resulting in the material being easily damaged locally during use, thus affecting its use.
[0004] For example, Zhang Hong et al. (Zhang Hong, Li Nan, Yan Wen. Effect of adding carbon fiber on the performance and microstructure of aluminum-carbon refractory materials [J]. Refractory Materials, 2014 (2): 106-110.) studied the effect of carbon fiber content on the performance and microstructure of aluminum-carbon refractory materials. They used fused white corundum as aggregate, fused white corundum fine powder and flake graphite as matrix, silicon powder as antioxidant, thermosetting phenolic resin as binder, and carbon fiber as additive to make aluminum-carbon refractory materials. The results showed that adding carbon fiber can improve the mechanical strength of the sample, but the problem of carbon fiber oxidation at high temperature has not been solved. At high temperature, it will oxidize in the sample and leave gaps, thereby reducing the practicality of the refractory sample. Therefore, there are certain risks in practical applications.
[0005] For example, Chen Bei et al. (Chen Bei, Ding Peidao, Zhou Zehua. Thermal shock resistance mechanism of fiber-reinforced aluminosilicate refractories [J]. Refractories, 2001, 35(6): 323-325, 328.) studied the effect of high aluminum fiber content on the thermal shock resistance mechanism of aluminosilicate refractories. Although the addition of high aluminum fiber can significantly improve the thermal shock resistance of refractory materials, the high aluminum fiber is expensive. Secondly, it is difficult for it to form a strong interface bond with aggregates and matrix, and it is very easy to peel off during multiple thermal shock cycles, resulting in the product being very easy to fail during service. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the present invention provides a quartz fiber toughened aluminum-carbon refractory material and a preparation method thereof. The aluminum-carbon refractory material prepared by the present invention has the advantages of high strength, good toughness, good thermal shock stability, excellent high temperature strength and long high temperature service life.
[0007] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is: A quartz fiber toughened aluminum-carbon refractory material, comprising a main material, quartz fiber and a binder; the main material comprises, by weight, 65-70% of sintered plate-shaped corundum particles, 10-15% of sintered plate-shaped corundum fine powder, 5-10% of carbon black, 1-3% of boron carbide, 1-6% of activated alumina, and 4-8% of silicon powder; The added weight of the quartz fiber is 0.1-0.3% of the weight of the main material; the added weight of the binder is 3-5% of the weight of the main material.
[0008] Furthermore, the Al2O3 content in the sintered plate-shaped corundum particles is greater than 99.5wt%, and includes two types of particles with a particle size of 1.0mm to 3.0mm and a particle size of 0.088mm to 1.0mm.
[0009] Furthermore, the Al2O3 content in the sintered plate-like corundum fine powder is greater than 99.5wt% and the particle size thereof is ≤74μm.
[0010] Furthermore, the C content in the carbon black is greater than 99 wt%, and its particle size is ≤74 μm; the B4C content in the boron carbide is greater than 99 wt%, and its particle size is ≤74 μm.
[0011] Furthermore, the particle size D of the activated alumina 5.0 ≤2.5μm, aluminum oxide content>99.8wt%; Si content in the silicon powder is>99.9wt%, and its particle size is ≤74μm.
[0012] Furthermore, the SiO2 content in the quartz fiber is greater than 90wt%, the fiber diameter is 2-8μm, and the fiber length is 6-12mm.
[0013] Furthermore, the binder is liquid phenolic resin, and the residual carbon rate is ≥35%.
[0014] The preparation method of the above-mentioned quartz fiber toughened aluminum-carbon refractory material comprises the following steps: Step (1), firstly, carbon black, boron carbide, activated alumina, silicon powder, quartz fiber and a binder of 1 to 2% by weight of the main material are placed in a closed high-power mixer according to a proportion, and heated and stirred for 2 to 4 hours to obtain a mixture I; Step (2), placing the sintered plate-shaped corundum particles into a stirring pot, adding the remaining binder at a uniform speed, and stirring for 10 to 15 minutes; then adding the sintered plate-shaped corundum fine powder and mixed material I, and continuing to stir for 10 to 15 minutes to obtain mixed material II; Step (3), trapping the mixed material II for 12 to 14 hours, then pressing and molding it, and drying it for 24 to 26 hours to obtain a dried green body; Step (4), heating the dried green body to 1200-1300°C in a carbon-buried atmosphere and keeping it at that temperature for 1-3 hours, then continuing to heat it to 1550-1650°C and keeping it at that temperature for 3-6 hours, and cooling it with the furnace to obtain a quartz fiber-reinforced aluminum-carbon refractory material.
[0015] Furthermore, in step (3), the mold is pressed at 150-200 MPa and dried at 200-220°C.
[0016] Furthermore, in step (4), the temperature is increased at a rate of 3 to 5°C / min in a carbon-buried atmosphere.
[0017] The beneficial effects of adopting the above technical solution are: 1. The present invention adopts a mixing and grinding process of sintered corundum aggregate, silicon powder, carbon black, boron carbide, quartz fiber and a binder. First, the matrix fine powder and the quartz fiber are premixed, and the quartz fiber is evenly distributed in the matrix fine powder through a suitable mixing time without damaging the fiber to obtain a mixture I. Then, the matrix fine powder with quartz fiber is evenly dispersed on the surface of the sintered corundum aggregate through a binder, and finally a mixture II with uniform composition and substances of the same composition and particle size per unit volume is formed.
[0018] 2. The present invention introduces quartz fiber with high toughness, high temperature resistance and excellent corrosion resistance into aluminum-carbon refractory materials, and achieves the optimized design of aluminum-carbon refractory products through high-temperature sintering. Specifically as follows: First, by introducing quartz fiber into the matrix fine powder, a mullite (3Al2O3-2SiO2) layer and mullite fiber are formed on its surface, thereby enhancing the interface bonding between the quartz fiber and the matrix; secondly, a closed strong high-heat mixing process is used to make the quartz evenly distributed in the blank, and also provide conditions for the quartz fiber to form a good bond with the aggregate surface. On the one hand, quartz fiber is different from other nano-scale fibers formed in situ. It has the characteristics of high strength and not easy to be oxidized, and can better fill the gaps in the refractory material, so that the quartz fiber has a better bridge with the aggregate and the matrix, which plays a role in strengthening and toughening. After heat treatment, the quartz fiber will react with the aluminum oxide in the matrix in situ to form a mullite layer, which significantly improves the bonding strength between the matrix and the fiber. At the same time, the high-temperature stable phase of mullite is formed in situ to improve the thermal shock and high-temperature performance of the material. It also avoids the problems of high temperature oxidation and loose interface bonding when reinforcing traditional carbon fiber and SiC fiber. On the other hand, quartz fiber has the function of preventing crack propagation. It is evenly dispersed in the matrix. When the blank breaks, it can absorb and disperse the stress concentration generated by the break and resist thermal shock due to its high tensile strength and elastic modulus, so as to achieve the purpose of improving the mechanical strength and high temperature stability of the blank.
[0019] 3. In the present invention, after the quartz fiber is heat-treated, it reacts with the aluminum source in the matrix to form a high-temperature stable mullite (3Al2O3-2SiO2) phase and is converted into mullite fiber, so that the introduced fiber is closely combined with the refractory matrix, and the thermal shock resistance of the product is better improved by forming a mullite (3Al2O3-2SiO2) layer with a low thermal expansion coefficient and good high-temperature thermal stability. Therefore, through a closed high-strength high-temperature mixing process and optimization of the interface between the fiber, aggregate and matrix, a fiber-reinforced aluminum-carbon refractory material with high strength, good toughness, excellent thermal shock resistance and long high-temperature service life is finally obtained.
[0020] The aluminum-carbon refractory prepared by the present invention is tested to have an apparent porosity of 15.21-16.51% and a bulk density of 3.05-3.23 g / cm 3 ; 1400℃ high temperature flexural strength is 25.3~35.8MPa; 1100~20℃ water cooling 3 times strength retention rate is 79~92%; fracture energy is 361.5~543.2J / m 2 .
[0021] Therefore, the present invention has the characteristics of simple process and low production energy consumption, and the prepared quartz fiber toughened aluminum-carbon refractory material has the characteristics of high strength, good thermal shock stability, excellent high-temperature strength and long high-temperature service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a microstructure diagram of the quartz fiber and the aggregate matrix combined after the aluminum-carbon refractory material prepared in Example 3 is heat-treated; Figure 2 This is a microstructure diagram of the quartz fiber and the aggregate matrix combined after the aluminum-carbon refractory material prepared in Example 4 is heat-treated; Figure 3 is the XRD pattern of the quartz fiber used in the examples. DETAILED DESCRIPTION
[0023] The requirements for the raw materials used in each embodiment are as follows and will not be repeated in the embodiments.
[0024] Sintered plate-shaped corundum particles: Al2O3 content> 99.5wt%, including two types of particles with a particle size of 1.0-3.0mm and a particle size of 0.088-1.0mm; Sintered plate-shaped corundum fine powder: Al2O3 content>99.5wt%, particle size ≤74μm; In carbon black: C content>99wt%, particle size≤74μm; In boron carbide: B4C content>99wt%, particle size≤74μm; Activated alumina: particle size D 5.0 ≤2.5μm, alumina content>99.8wt%; Silicon powder: Si content>99.9wt%, particle size≤74μm.
[0025] Quartz fiber: SiO2 content>90wt%, fiber diameter 2~8μm, fiber length 6~12mm. Example 1
[0026] The steps of the preparation method of the quartz fiber toughened aluminum-carbon refractory material in this embodiment are as follows: The main ingredients are 70wt% of sintered plate-shaped corundum particles, 13wt% of sintered plate-shaped corundum fine powder, 1wt% of activated alumina fine powder, 7wt% of carbon black fine powder, 3wt% of boron carbide fine powder, and 6wt% of silicon powder, and 0.1wt% of quartz fiber and 3wt% of phenolic resin are added; Step (1), firstly, placing 7wt% of carbon black fine powder, 3wt% of boron carbide fine powder, 1wt% of activated alumina fine powder, 6wt% of silicon powder, 0.1wt% of quartz fiber by weight of the main material and 1wt% of phenolic resin by weight of the main material into a closed high-power mixer and heating and stirring for 2 hours to obtain a mixture I; Step (2), placing the sintered plate-shaped corundum particles into a stirring pot, and adding phenolic resin in an amount of 2 wt% of the main material at a uniform speed, stirring for 10 minutes, and then adding the sintered plate-shaped corundum fine powder and mixed material I, and continuing to stir for 15 minutes to obtain mixed material II; Step (3), trapping the mixed material II for 12 hours, pressing and molding under 150 MPa, and drying at 200° C. for 24.5 hours to obtain a dried green body; Step (4), heating the dried green body to 1220°C at a rate of 3°C / min in a carbon-buried atmosphere and keeping the temperature therefor for 2 hours, then continuing to heat the green body to 1550°C at the same rate and keeping the temperature therefor for 3 hours, and cooling the green body with the furnace to obtain a quartz fiber-reinforced aluminum-carbon refractory material. Example 2
[0027] The steps of the preparation method of the quartz fiber toughened aluminum-carbon refractory material in this embodiment are as follows: The main ingredients are 65wt% of sintered plate-shaped corundum particles, 15wt% of sintered plate-shaped corundum fine powder, 2wt% of activated alumina fine powder, 10wt% of carbon black fine powder, 2wt% of boron carbide fine powder, and 6wt% of silicon powder, and 0.6wt% of quartz fiber and 4wt% of phenolic resin are added; Step (1), firstly, placing the 10wt% carbon black fine powder, 2wt% boron carbide fine powder, 2wt% activated alumina fine powder, 6wt% silicon powder, 0.7wt% quartz fiber by weight of the main material and 2wt% phenolic resin by weight of the main material into a closed high-power mixer, heating and stirring for 3 hours to obtain a mixture I; Step (2), placing the sintered plate-shaped corundum particles into a stirring pot, and adding phenolic resin in an amount of 2 wt% of the weight of the main material at a uniform speed, stirring for 15 minutes, and then adding the sintered plate-shaped corundum fine powder and mixed material I, and continuing to stir for 10 minutes to obtain mixed material II; Step (3), trapping the mixed material II for 13 hours, pressing and molding under the condition of 180 MPa, and drying at 210° C. for 25 hours to obtain a dried green body; Step (4), heating the dried green body to 1260°C at a rate of 4°C / min in a carbon-buried atmosphere and keeping the temperature therefor for 1 hour, then continuing to heat the green body to 1600°C at the same rate and keeping the temperature therefor for 4 hours, and cooling the green body with the furnace to obtain a quartz fiber-reinforced aluminum-carbon refractory material. Example 3
[0028] The preparation method and materials used for the quartz fiber toughened aluminum-carbon refractory material of this embodiment are as follows: The main ingredients are 69wt% of sintered plate-shaped corundum particles, 10wt% of sintered plate-shaped corundum fine powder, 6wt% of activated alumina fine powder, 5wt% of carbon black fine powder, 2wt% of boron carbide fine powder, and 8wt% of silicon powder, and 0.9wt% of quartz fiber and 5wt% of phenolic resin are added; Step (1), firstly, 5wt% of the carbon black fine powder, 2wt% of the boron carbide fine powder, 6wt% of the activated alumina fine powder, 8wt% of the silicon powder, 0.3wt% of the main material weight of the quartz fiber and 1wt% of the main material weight of the phenolic resin are placed in a closed high-power mixer and heated and stirred for 4 hours to obtain a mixture I; Step (2), placing the sintered plate-shaped corundum particles into a stirring pot, adding phenolic resin in an amount of 4 wt% of the main material at a uniform speed, stirring for 12 minutes, then adding the sintered plate-shaped corundum fine powder and mixed material I, and continuing to stir for 13 minutes to obtain mixed material II; Step (3), trapping the mixed material II for 12.5 hours, pressing and molding at 200 MPa, and drying at 220° C. for 26 hours to obtain a dried green body; Step (4), heating the dried green body to 1300°C at a rate of 5°C / min in a carbon-buried atmosphere and keeping the temperature therefor for 3 hours, then continuing to heat the green body to 1650°C at the same rate and keeping the temperature therefor for 5.5 hours, and cooling the green body in the furnace to obtain a quartz fiber-reinforced aluminum-carbon refractory material. Example 4
[0029] The steps of the preparation method of the quartz fiber toughened aluminum-carbon refractory material in this embodiment are as follows: The main ingredients are 68wt% of sintered plate-shaped corundum particles, 12wt% of sintered plate-shaped corundum fine powder, 5wt% of activated alumina fine powder, 10wt% of carbon black fine powder, 1wt% of boron carbide fine powder, and 4wt% of silicon powder, and 0.3wt% of quartz fiber and 4wt% of phenolic resin are added; Step (1), firstly, 10wt% of carbon black fine powder, 1wt% of boron carbide fine powder, 5wt% of activated alumina fine powder, 4wt% of silicon powder, 0.3wt% of quartz fiber by weight of the main material and 1.5wt% of phenolic resin by weight of the main material are placed in a closed high-power mixer and heated and stirred for 4 hours to obtain a mixture I; Step (2), placing the sintered plate-shaped corundum particles into a stirring pot, adding phenolic resin in an amount of 2.5 wt% of the main material at a uniform speed, stirring for 11 minutes, then adding the sintered plate-shaped corundum fine powder and mixed material I, and continuing to stir for 14 minutes to obtain mixed material II; Step (3), trapping the mixed material II for 13.5 hours, pressing and molding under the condition of 180 MPa, and drying at 220° C. for 24 hours to obtain a dried green body; Step (4), heating the dried green body to 1200°C at a rate of 4°C / min in a carbon-buried atmosphere and keeping the temperature therefor for 3 hours, then continuing to heat the green body to 1590°C at the same rate and keeping the temperature therefor for 6 hours, and cooling the green body with the furnace to obtain a quartz fiber-reinforced aluminum-carbon refractory material. Example 5
[0030] The steps of the preparation method of the quartz fiber toughened aluminum-carbon refractory material in this embodiment are as follows: The main ingredients are 67wt% of sintered plate-shaped corundum particles, 14wt% of sintered plate-shaped corundum fine powder, 4wt% of activated alumina fine powder, 9wt% of carbon black fine powder, 1wt% of boron carbide fine powder, and 5wt% of silicon powder, and 0.5wt% of quartz fiber and 5wt% of phenolic resin are added; Step (1), firstly, placing 9wt% of carbon black fine powder, 1wt% of boron carbide fine powder, 4wt% of activated alumina fine powder, 5wt% of silicon powder, 0.2wt% of quartz fiber by weight of the main material and 2wt% of phenolic resin by weight of the main material into a closed high-power mixer, heating and stirring for 3.5 hours to obtain a mixture I; Step (2), placing the sintered plate-shaped corundum particles into a stirring pot, adding phenolic resin in an amount of 3 wt% of the main material at a uniform speed, stirring for 14 minutes, then adding the sintered plate-shaped corundum fine powder and mixed material I, and continuing to stir for 11 minutes to obtain mixed material II; Step (3), trapping the mixed material II for 14 hours, pressing and molding at 190 MPa, and drying at 210° C. for 26 hours to obtain a dried green body; Step (4), heating the dried green body to 1250°C at a rate of 5°C / min in a carbon-buried atmosphere and keeping the temperature for 1 hour, then continuing to heat the green body to 1645°C at the same rate and keeping the temperature for 5 hours, and cooling the green body with the furnace to obtain a quartz fiber-reinforced aluminum-carbon refractory material.
[0031] The properties of the quartz fiber toughened aluminum-carbon refractory materials prepared in the above embodiments are shown in Table 1.
[0032]
[0033] from Figure 1 , Figure 2 It can be seen that after high-temperature heat treatment, the mullite layer and mullite fiber are in-situ generated on the surface of the quartz fiber, and the interface bonding between the quartz fiber, the matrix and the aggregate is good, which has a good toughening effect on the aluminum-carbon refractory material.
[0034] from Figure 3 It can be seen that the XRD spectrum of the quartz fiber used in the present invention shows a diffraction characteristic peak of the aluminum oxide (214) crystal plane.
[0035] Therefore, the present invention introduces quartz fibers into aluminum-carbon refractory materials, so that the fibers and the refractory matrix form a mullite layer in situ, thereby producing a tight bond, thereby achieving the purpose of improving the mechanical strength and high-temperature stability of the blank, and ultimately producing fiber-reinforced aluminum-carbon refractory materials with high strength, good toughness, excellent thermal shock resistance and long high-temperature service life.
Claims
1. A quartz fiber toughened aluminum-carbon refractory material, characterized in that: The invention comprises a main material, quartz fiber and a binder; the main material comprises, by weight, 65-70% of sintered plate-shaped corundum particles, 10-15% of sintered plate-shaped corundum fine powder, 5-10% of carbon black, 1-3% of boron carbide, 1-6% of activated alumina and 4-8% of silicon powder; The added weight of the quartz fiber is 0.1-0.9% of the weight of the main material; the added weight of the binder is 3-5% of the weight of the main material.
2. The quartz fiber toughened aluminum-carbon refractory material according to claim 1, characterized in that: The Al2O3 content in the sintered plate-shaped corundum particles is greater than 99.5wt%, and the particles include two types of particles with a particle size of 1.0mm to 3.0mm and a particle size of 0.088mm to 1.0mm.
3. The quartz fiber toughened aluminum-carbon refractory material according to claim 2, characterized in that: The Al2O3 content in the sintered plate-shaped corundum fine powder is greater than 99.5wt% and the particle size thereof is less than or equal to 74μm.
4. The quartz fiber toughened aluminum-carbon refractory material according to claim 3, characterized in that: The C content in the carbon black is greater than 99wt%, and its particle size is ≤74μm; the B4C content in the boron carbide is greater than 99wt%, and its particle size is ≤74μm.
5. The quartz fiber toughened aluminum-carbon refractory material according to claim 4, characterized in that: The activated alumina particle size D 5.0 ≤2.5μm, aluminum oxide content>99.8wt%; Si content in the silicon powder is>99.9wt%, and its particle size is ≤74μm.
6. The quartz fiber toughened aluminum-carbon refractory material according to claim 5, characterized in that: The SiO2 content in the quartz fiber is greater than 90wt%, the fiber diameter is 2-8μm, and the fiber length is 6-12mm.
7. The quartz fiber toughened aluminum-carbon refractory material according to claim 6, characterized in that: The binder is liquid phenolic resin, and the residual carbon rate is ≥35%.
8. A method for preparing a quartz fiber toughened aluminum-carbon refractory material according to any one of claims 1 to 7, characterized in that: The steps include: Step (1), firstly, carbon black, boron carbide, activated alumina, silicon powder, quartz fiber and a binder of 1 to 2% by weight of the main material are placed in a closed high-power mixer according to a proportion, and heated and stirred for 2 to 4 hours to obtain a mixture I; Step (2), placing the sintered plate-shaped corundum particles into a stirring pot, adding the remaining binder at a uniform speed, and stirring for 10 to 15 minutes; then adding the sintered plate-shaped corundum fine powder and mixed material I, and continuing to stir for 10 to 15 minutes to obtain mixed material II; Step (3), trapping the mixed material II for 12 to 14 hours, then pressing and molding it, and drying it for 24 to 26 hours to obtain a dried green body; Step (4), heating the dried green body to 1200-1300°C in a carbon-buried atmosphere and keeping it at that temperature for 1-3 hours, then continuing to heat it to 1550-1650°C and keeping it at that temperature for 3-6 hours, and cooling it with the furnace to obtain a quartz fiber-reinforced aluminum-carbon refractory material.
9. The method for preparing the quartz fiber toughened aluminum-carbon refractory material according to claim 8, characterized in that: The step (3) comprises the steps of: performing mechanical compression molding at 150-200 MPa and drying at 200-220°C.
10. The method for preparing the quartz fiber toughened aluminum-carbon refractory material according to claim 8 or 9, characterized in that: In the step (4), the temperature is increased at a rate of 3 to 5°C / min in a carbon-buried atmosphere.
Citation Information
Patent Citations
A multi-fiber reinforced magnesium-aluminum-carbon refractory material and its preparation process
CN107512902B
Ceramic composition and production of ceramic plate
JP1996333176A
Cited By
Alumina ceramic with low thermal expansion coefficient and preparation method thereof
CN120903917A